Joint Analysis of Multiple Omics to Describe the Biological Characteristics of Resistant Hypertension - Shanshan Wang; Yuanlong Hu; Yuqi Wang; Yueyue Song; Dan Liang; Jiufeng Yin; Yunlun Li; Wenqing Yang; Dan Zhang (The Journal of Clinical Hypertension)
Abstract Resistant hypertension (RH) may cause severe target organ damage and poses significant challenges in the field of hypertension prevention and treatment. Mining biological characteristics is crucial for exploring the pathogenesis of RH and for early diagnosis and treatment. Although several single‐omics studies have been conducted on RH, its complex pathogenesis has only been partially elucidated. In this study, metabolomics, proteomics, and transcriptomics were jointly analyzed in healthy subjects and patients with hypertension and RH. The multi‐omics analysis found that differential substances of RH were enriched in the HIF‐1 signaling pathway and that differential substances such as ascorbic acid, reduced glutathione (GSH), choline, citric acid, transferrin receptor (TfR), Egl‐9 family hypoxia‐inducible factor 2 (EGLN2), and glutathione peroxidase 1 (GPX1) were screened out. The results of intergroup comparisons were as follows: RH versus N: ascorbic acid (Fold Change (FC):0.42, p < 0.01), GSH (FC:0.65, p < 0.05), choline (FC:1.32, p < 0.05), citric acid (FC:0.48, p < 0.001), TfR (FC2.32, p < 0.001), GPX1 (FC:16.02, p < 0.001), EGLN2 (FC:0.76, p < 0.001); RH versus EH: ascorbic acid (FC:0.52, p < 0.05), GSH (FC:0.55, p < 0.05), choline (FC:1.28, p < 0.05), citric acid (FC:0.59, p < 0.001), TfR (FC:1.71, p < 0.001), GPX1 (FC:2.11, p < 0.05), EGLN2 (FC:0.76, p < 0.05). These differential substances may reflect the biology of RH. This study provides multi‐omics analysis for a deeper understanding of the complex molecular characteristics of RH, providing new insights into the pathogenesis, early diagnosis, and precise treatment of the disease.